ANALISIS FRAMING PEMBERITAAN WACANA PERPANJANGAN MASA JABATAN PRESIDEN JOKO WIDODO (Berita Detik.com dan Kompas.com Periode Agustus-Desember 2022) - Raihan Achmad Rifandi (2023)
It is phenomenal to report on the extension of the President's term of office into three terms in the mass media. Since the reform era, the term of office for state leaders has been limited to two terms by amending the 1945 Constitution, specifically Article 7. This was done to prevent abuse of power by previous presidents. President Joko Widodo issued a discourse that he would advance to lead for three terms. The purpose of this research is to understand and find out how the framing and prominence aspects of online media Detik.com and Kompas.com are used in responding to the discourse of President Joko Widodo's three periods. The selected news object focuses on the issue of extending President Joko Widodo's term of office into three terms. The choice of media is motivated by the size and influence of the media in Indonesia. Entman's framing analysis method is used in this study to study how the media builds and emphasizes certain aspects of their coverage. The findings from this study are that Detik.com and Kompas.com are neutral in covering this event. Detik.com covered this event much earlier before the Musra Forum meeting held in Bandung, while Kompas.com covered after the event was held. On the other hand, Detik.com covers all phenomena from this discourse, including the support received by President Joko Widodo, Kompas.com does not cover the support received by President Joko Widodo and only covers the opposition to President Joko Widodo.